Ultrasound investigation at examination of gastro-intestinal tract at combined trauma - A. S. Yermolov; O. A. Alekseyechkina; Ye. S. Vladimirova; G. P. Titova; V. M. Abuchina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To determine ultrasound characteristics of gastro-intestinal tract (GIT) at combined trauma.Material and methods. Data of ultrasound investigations (US) in 48 patients with combined trauma (36 men, 12 women, aged 20–50 years) with disorders of gastro-intestinal function were analyzed. Combined trauma (of chest, abdomen, pelvis, spine, extremities) was diagnosed in 41 patients, in 7 cases closed craniocerebral trauma prevailed. All patients underwent US to rule out damage of abdominal organs at hospital admission. Patients have been divided into two groups: patients of the first (n=27) had no damage of abdominal organs, no surgery was carried out, patients of the second group had combined trauma and closed injury of abdomen (n=21) and subsequently abdominal surgery was performed. Investigation of abdominal organs was carried out by medium class ultrasound devices with convex (3,5 mHz) and linear (7,5 mHz) probes. Abdominal organs were examined according to the standard protocol for signs of traumatic damage, presence of free fluid, retroperitoneum was examined as well. Resected portions of the small intestine with adjacent damaged mesentery were subject to comparative histological examination at closed abdominal injury cases.Results. In 27 patients of the first group US revealed signs of ileus in posttraumatic period. In 22 patients US-signs of dynamic ileus were revealed on a background of retroperitoneal hematoma, in 7 cases dynamic examination revealed its enlargement, in the other 7 cases retroperitoneal hematoma was small with tendency to spontaneous resolution. In 6 cases mesenteric hematoma of the small intestine, extending to retroperitoneum was found out. In 2 patients with pelvic bones fracture hematoma of sigmoid colon mesentery was visualized. Five patients had spinal trauma. In posttraumatic period in 19 of 27 first group patients with onset of multiorgan failure dynamic US demonstrated liver, spleen and kidney enlargement. In 8 patients gastric stasis was revealed at the 9 day after trauma, in 3 cases — on the 10–14 day signs of pseudomembranous colitis were found out. In the second group at the 3rd day after surgery disorder of motor and evacuatory function of GIT was found. At US control in 11 patients with small intestine mesentery trauma signs of dynamic ileus were revealed, in 4 of them after resection of intestinal segment signs of mesenteric circulation disorder at the early postoperative period were found out. As a result of conservative therapy paresis of the gut was eliminated. In 2 patients after operation for splenic rupture and in 2 patients with urinary bladder trauma dynamic smallintestinal ileus was diagnosed with subsequent resolution according to clinical and ultrasound data after conservative treatment. In 2 of 6 patients with intestinal trauma after suture application pharmaceutical therapy resulted in resolution of intestinal paresis. In 1 of 4 patients with resection of small intestine and signs of dynamic ileus intestinal function was restored under conservative treatment. Three patients with mechanical smallintestinal obstruction on a background of abdominal adhesions were operated.Conclusions. The dynamic ultrasound investigation in posttraumatic period after combined trauma helps to differentiate dynamic and mechanical smallintestinal obstruction and determine indications to surgical intervention in early terms. Application of this method allows to reveal intestinal posttraumatic changes on background of dynamic smallintestinal obstruction that may require revision of treatment approach. US in postoperative period at hematomas of smallintestinal mesentery without disorder of integrity of intestine, reveals disorders of gastrointestinal motility and development of paresis of intestine which aggravates circulation disorders in intestinal wall and can result in irreversible changes. Color Doppler flow mapping mode of ultrasound investigation at extensive hematomas of mesentery helps to detect thrombosis of mesenteric veins, occlusion of stem arteries that provides surgeons with essential information to choose treatment tactics, and in some cases to predict course of disease.